ANALISIS PENGARUH BAURAN PEMASARAN TERHADAP MINAT BELI MELALUI VARIABEL CITRA MEREK PRODUK PIERO - Bagas Herlambang Autoprawiro; Berta Bekti Retnawati (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2020)
The shoe industry in Indonesia collided with each other to strengthen its brand in various ways to attract consumer buying interest. This study was aimed to examine the efforts of the Piero brand to create a buying interest in consumers through several marketing mix variables as variables that represent independent and intervening variable brand image. The population of this research were the followers of the @piero_jateng_diy account who took 30 samples from followers of the account. The sampling used was purposive sampling. Data analysis in this study was using descriptive analysis, multiple regression test, determination coefficient test (R2), t test, F test, and path analysis test. Descriptive analysis had shown the average answer agreed on each tested variable, with a coefficient of determination (R2) of 91.3% and multiple regression resulting in a regression equation Y = -1.360+ 0.282 X1 + 0.383 X2. The first to third hypotheses test which used the t test showed the effect of significance below 0.05 and test the four hypotheses used the F test to showed the effect of independent variables on the dependent variable with a significance below 0.05. The fifth hypotheses test was using path analysis test to produce that mediating variables can provide indirect influence on independent variables on the dependent variable.Piero must strengthen in terms of the availability of goods, easy to remember the Piero brand in the minds of consumers and strengthen it to make Piero one of the consumers' choices.